Forward Kinematics Analysis of Quadruped Bionic Robot with Spine based on Dimensionality-reduction Method - Wang Liangwen; Mu Yalin; Yue Lei; Li Hongpeng; Wang Xinjie; Du Wenliao (Jixie chuandong)
For coordinating the body change and leg movement to promote jump and over-obstacle ability of a bionic robot,a new type of quadruped bionic robot configurations with spine is introduced. On this basis,the forward kinematics problem of this kind of the robot is studied. Firstly,according to the structure of the robot,the motion equations are established which contain the all driving angles. The motion equations contain many redundant drive angles,which is very difficult to solve the redundant drive angles,a dimensionality-reduction method is adopted. By using the dimensionality-reduction method,one of the formulas is translated to the constraint condition,the iteration procedure is used for the rest of equation sets to seek solutions of the redundant drive angles which satisfy the constraint condition. On this basis,the pose of mass center for the quadruped bionic robot with spine is solved and analyzed. An example is given to illustrate the process,this research is helpful to accelerate the use of this kind of robot.